Răspuns :
[tex]\left(\frac{9}{2}-\frac{1}{3}\right)\frac{6}{10}+\frac{1}{8}[/tex]
[tex]\frac{6}{10}=\frac{3}{5} =\frac{2\cdot \:3}{10} =\frac{2\cdot \:3}{2\cdot \:5} =\frac{3}{5}[/tex]
[tex]=\left(\frac{9}{2}-\frac{1}{3}\right)\frac{3}{5}+\frac{1}{8}[/tex]
[tex]=\left(\frac{27}{6}-\frac{2}{6}\right)\frac{3}{5}+\frac{1}{8}[/tex]
[tex]=\frac{27-2}{6}\cdot \frac{3}{5}+\frac{1}{8}[/tex]
[tex]=\frac{25}{6}\cdot \frac{3}{5}+\frac{1}{8}[/tex]
[tex]\frac{25}{6}\cdot \frac{3}{5} =\frac{5\cdot \:5}{6}\cdot \frac{3}{5} =\frac{5}{6}\cdot \frac{3}{1} =\frac{5}{3\cdot \:2}\cdot \frac{3}{1}=\frac{5}{2}[/tex]
[tex]=\frac{5}{2}+\frac{1}{8}[/tex]
[tex]=\frac{20}{8}+\frac{1}{8}[/tex]
[tex]=\frac{20+1}{8}[/tex]
[tex]=\frac{21}{8}[/tex]
Sper că te-am ajutat!
Succes!